Order of Magnetic Transitions in La(Fe1-xSix)13 Induced by Random Anisotropy - Kim Anh, Do Thi; Thi Kim Oanh, Nguyen; Tu Niem, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 42 No 2DO - 10.25073/2588-1124/vnumap.5134, 2026)
The temperature dependence of the magnetic moment in La(Fe 1-x Si x ) 13 compounds reveals the presence of both first-order and second-order magnetic phase transitions. The nature of the transition is governed by variations in the Si concentration, which induce significant modifications in the Fe I –Fe II interactions between Fe atoms occupying two non-equivalent sites. These effects can be effectively modeled as a form of random anisotropy, the resulting behavior of which is accurately described within the framework of the Blume-Capel model. Monte Carlo simulations demonstrate that the evolution from a first-order to a second-order magnetic transition in La(Fe 1-x Si x ) 13 compounds can be consistently reproduced by maintaining a fixed anisotropy probability p while systematically reducing the corresponding anisotropy amplitude D , yielding good agreement with experimental trends.